MANAJEMEN KELAS DALAM MENINGKATKAN MINAT LITERASI MEMBACA SISWA SEKOLAH DASAR - Dinny Mardiana; -, Nendi Wahyudi; Irma Rismawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze how classroom management is implemented to enhance elementary school students' reading literacy interest at SDN Selaawi, Cianjur Regency. This research employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and document analysis. The results indicate that classroom management was carried out through literacy planning, organizing the roles of teachers and school, implementing activities such as reading corners and the “15-Minute Reading” program, as well as evaluation through reading tests, behavior observation, and questionnaires. Main challenges such as limited facilities and funding were overcome through community collaboration and local resource optimization. The structured and adaptive implementation of classroom management proved effective in significantly increasing students' reading interest and literacy engagement.